HAKIKAT KEBENARAN DAN KESETARAAN YANG DICARI DALAM PRINSIP MENDENGAR PIHAK-PIHAK : The Essence of Truth and Equality Sought In The Principle of Hearing The Parties - Dwi Handayani; Handayani, Dwi (Jurnal Hukum PRIORIS, 2023)
In civil litigation, the phenomenon of judgments that do not reflect the fairness or balance of the litigants undermines justice and legal certainty. Although the legal principle of hearing both parties is a manifestation of balance in judicial procedures, the judge's decision does not provide strict punishment for violations of legal principles, only violations of the code of ethics so that they are often violated in practice. Basically, this process focuses on the truth that will be sought and found for a fair and balanced trial in a civil case. This research uses a qualitative approach, with primary and secondary data sources which will then be analyzed with analytical descriptive techniques to answer legal issues. The results of the study concluded that in principle the judge looks for formal (relative) truth in the evidence presented by the parties, but if the judge is not sure it is okay to make a legal breakthrough by seeking material truth in the evidentiary process at trial to get a fair and balanced verdict. This study recommends that judges should actively seek truth in the civil cases they handle even though civil judges are civil judges in principle